On the SCFDE uplink alternative to OFDM in a massive MU-MIMO context - Torres, Paulo (2019)
This paper deals with Single Carrier (SC)/Frequency Domain Equalization (FDE) as an uplink alternative to Orthogonal Frequency Division Multiplexing (OFDM) for a Multi User (MU)-Multi-Input Multi-Output (MIMO) system where a ”massive MIMO” approach is adopted. In this context, either an optimum Minimum Mean-Squared Error (MMSE) linear detector or appropriate reduced-complexity linear detection techniques are considered. Regarding performance evaluation by simulation, two semi-analytical methods are proposed - one method in the optimum (MMSE) case and the other one in the reduced-complexity cases. This paper includes performance results for uncoded 4 Quadrature Amplitude Modulation (QAM) SC/FDE transmission and a MU-MIMO channel with uncorrelated Rayleigh fading, under the assumptions of perfect power control and perfect channel estimation.The accuracy of performance results obtained through the semi-analytical simulation methods is assessed by means of parallel conventional Monte Carlo simulations. The performance results are discussed in detail and we also emphasize the achievable ”massive MIMO” effects, even for the reduced complexity detection techniques, provided that the number of BS antennas is much higher than the number of antennas which are jointly employed in the terminals of the multiple autonomous users. Appropriate ”SC/FDE vs OFDM” comparisons are also included in this discussion of performance results.